ASSESSING THE IMPLEMENTATION OF MURABAHAH–WAKALAH HYBRID CONTRACTS IN SHARIA FINTECH: COMPLIANCE ANALYSIS OF DSN-MUI FATWA NO. 117/2018 IN INDONESIA - Alisah, Juliah; Nurhidayati, Dini; Eyicha; Hartini, Kustin; Sunarti, Gustiya; Pramadeka, Katra (Proceeding International Conference on Islam and Civilization (ICONIC), 2026)
This study aims to analyze the implementation of the murabahah–wakalah hybrid contract in Islamic fintech in Indonesia and assess its compliance with the DSN-MUI Fatwa No. 117/DSN-MUI/II/2018. The research method used is descriptive qualitative with a literature study approach, using primary data from the DSN-MUI fatwa and OJK regulations, as well as secondary data from academic literature. The results show that the murabahah–wakalah mechanism has been implemented in accordance with sharia principles through the stages of granting power of attorney, transfer of ownership, and sale and purchase agreement with an agreed profit margin. However, practice in the field still faces obstacles such as low user literacy, less than optimal clarity of digital contracts, and less than optimal supervision by the Sharia Supervisory Board (DPS). The research gap lies in the lack of studies that comprehensively examine the operational compliance of multi-contracts with the formal DSN-MUI fatwa. Therefore, this study makes an important contribution to strengthening the literature related to sharia compliance in the fintech sector. The implications of this research emphasize the importance of developing more detailed technical regulations, enhancing the role of the Sharia Supervisory Board (DPS), and providing ongoing education to strengthen Sharia compliance and the sustainability of the Sharia fintech industry in Indonesia.